Challenges in updating national guidelines and essential medicines lists in Sub‐Saharan African countries to include WHO‐recommended postpartum hemorrhage medicines. (28th June 2022) - Ng'ang'a, Joyce; Chitimbe, Tabeth; Mburu, Rosemary; Rushwan, Sara; Ntirushwa, David; Chinery, Lester; Gülmezoglu, A. Metin
Abstract: Despite the 2017 WHO recommendations on tranexamic acid (TXA) for the treatment of postpartum hemorrhage (PPH), the 2018 uterotonic recommendations (which included heat‐stable carbetocin (HSC) for the prevention of PPH) and their inclusion in the WHO Essential Medicines List (EML), both drugs are still underused or not used at all to manage PPH in many countries with a high burden. HSC is currently being registered in low‐ and middle‐income countries and its policy inclusion is limited and slow. TXA (also heat stable) is available in many countries but is not registered for PPH treatment, which may have contributed to the delay in its inclusion in national guidelines and EMLs. For both drugs, national guidelines will need to be revised and updated for their optimal uptake. We implemented an advocacy initiative to accelerate the necessary normative policy change to ensure access to quality‐assured and heat‐stable medicines for the prevention and treatment of PPH in Sub‐Saharan African countries. Our initiative aimed to raise awareness of the importance of recently recommended medicines for the prevention and treatment of PPH and support the process to update PPH guidelines and EMLs to include these drugs. We highlight the lessons learned during the initiative, including the challenges and opportunities identified in updating PPH policies at the national level. Synopsis: Challenges in achieving timely national policy updates to address prevention and treatment of postpartum hemorrhage (PPH) are highlighted, with the goal of reducing maternal morbidity and mortality in countries with a high burden of PPH.